Multiple Sclerosis and Obesity: Possible Roles of Adipokines - José de Jesús Guerrero-García; Lucrecia Carrera-Quintanar; Rocío Ivette López-Roa; Ana Laura Márquez-Aguirre; Argelia Esperanza Rojas-Mayorquín; Daniel Ortuño-Sahagún (Hindawi Limited, 2016)
Multiple Sclerosis (MS) is an autoimmune disorder of the Central Nervous System that has been associated with several environmental factors, such as diet and obesity. The possible link between MS and obesity has become more interesting in recent years since the discovery of the remarkable properties of adipose tissue. Once MS is initiated, obesity can contribute to increased disease severity by negatively influencing disease progress and treatment response, but, also, obesity in early life is highly relevant as a susceptibility factor and causally related risk for late MS development. The aim of this review was to discuss recent evidence about the link between obesity, as a chronic inflammatory state, and the pathogenesis of MS as a chronic autoimmune and inflammatory disease. First, we describe the main cells involved in MS pathogenesis, both from neural tissue and from the immune system, and including a new participant, the adipocyte, focusing on their roles in MS. Second, we concentrate on the role of several adipokines that are able to participate in the mediation of the immune response in MS and on the possible cross talk between the latter. Finally, we explore recent therapy that involves the transplantation of adipocyte precursor cells for the treatment of MS.